ENVIRONMENTAL IMPACTS OF WORKING CONDITIONS IN PAINT FACTORIES WORKERS IN THE HASHEMITE KINGDOM OF JORDAN (FIELD STUDY) - Assaf, D.Abdel Mutti; Alswalha, D.Ayyoub (European Scientific Journal, ESJ, 2013)
This paper attempts to analyze the factors that affect the internal and external environmental conditions on workers of the Jordanian paints factories, in terms of the degree of satisfaction with these conditions and their impact on the case of the general satisfaction of these institutions, As well as the impact on productivity and career on the state of job rotation. The results showed that there is a strong relation between these variables and employee satisfaction and stability, especially the case of the internal conditions, with minor variations among worker categories, but the effects on productivity were not strong. The empirical findings will certainly help both researchers and practitioners to integrate the internal and external environmental conditions on workers of the Jordanian paints factories In order to get a better understanding of the degree of satisfaction.